Kemampuan Berpikir Kritis Matematis dan Adversity Quotient Siswa SMP - Wahyu Hidayat; Veny Triyana Andika Sari (Jurnal Elemen, 2019)
This study is experimental research that aims to know about the influence Adversity Quotient (AQ) of the achievement students’ mathematical critical thinking ability. The population of this study is the students of Junior High School in Cimahi City, West Java, Indonesia; while the sample is 79 students selected purposively. The instruments of this study are tests and non-tests. They are based on the assessment of good characteristics towards students' mathematical critical thinking abilities, while the non-test instrument is based on the assessment of good characteristics towards AQ. The results show that: (1) AQ gives positive influence to the achievement students’ mathematical critical thinking ability with the influence of 61%, while the rest of it (39%) is influenced by other factors outside AQ; (2) there are differences in achievement in the students’ mathematical critical thinking ability based on AQ level (climber, camper, quitter).